2014
DOI: 10.9755/ejfa.v26i7.17513
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions of the Tunisian Ziziphus jujuba oil

Abstract: Thirteen fatty acids were identified from the pulps of four Tunisian Ziziphus jujuba ecotypes (Sfax, Choutrana, Mahres and Mahdia), using capillary gaseous chromatography method. These oils presented 8.31% to 12.35% of dry weights. Compared to the other ecotypes, Mahres and Choutrana were the richest of the oleic acid. The palmitic acid was the most important compound of the Sfax ecotype. Unsaturated fatty acids ranged from 62.63% to 72.40% of the total fatty acids of each ecotype. So a ratio of the unsaturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Stigmasterol and ␤-sitosterol were the predominant sterols in leaf extracts. This was confirmed by Elaloui et al (2011Elaloui et al ( , 2014a in Z. jujuba pulp and seed extracts. She obtained 27.32 mg/100 g and 16.12 mg/100 g for stigmasterol and 214.32 mg/100 g and 10.65 mg/100 g for ␤-sitosterol in seeds and pulp, respectively.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Stigmasterol and ␤-sitosterol were the predominant sterols in leaf extracts. This was confirmed by Elaloui et al (2011Elaloui et al ( , 2014a in Z. jujuba pulp and seed extracts. She obtained 27.32 mg/100 g and 16.12 mg/100 g for stigmasterol and 214.32 mg/100 g and 10.65 mg/100 g for ␤-sitosterol in seeds and pulp, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…used for medicinal and pharmaceutical applications (hypotensive, antihypoxia and hypothermie). make up 12.35% and 37.5% of the dry weight of the pulp and seeds, respectively (Elaloui et al, 2011(Elaloui et al, , 2014a. Others works have shown that the compounds extracted from Ieaves are limited and fragmented (Zhang et al, 2014).…”
Section: E-mail Address: Lam2081@yahoofr(a Laamouri)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other sterols notably stigmasterol, Δ 5 -avenasterol, Δ 5 , 24-stigmatadienol, and cholesterol are present in small quantities. Total sterols content in Z. lotus seed oil was 285.03 mg/100 g. Compared to other vegetable oils, this content is better than Z. jujuba oil (18.56 mg/100 g) [10] and virgin oil (150 mg/100 g) [59] but lower than those measured in Z. zizyphus (291.82 mg/100 g) [54] and soy oil (350 mg/100 g) [60]. It is important to indicate that there is no available data on the sterol content in the other parts of Z. lotus ; this issue remains to be determined.…”
Section: Classification Of Natural Biomolecules Of Z Lotusmentioning
confidence: 99%
“…In addition, in traditional medicine, both in North Africa and Middle East, several parts of Z. lotus are given as antiurinary troubles agents, antidiabetes, skin infections, antifever, antidiarrhea, insomnia agents, sedative, bronchitis, and hypoglycemic activities [69]. On the other hand, this plant offers a delicious read fruit (jujube) that was consumed fresh, dried, and processed as food by local populations in substantial amounts [10]. …”
Section: Introductionmentioning
confidence: 99%